TINJAUAN YURIDIS TERHADAP PIDANA KURUNGAN OLEH ANAK DIBAWAH UMUR YANG MENGGUNAKAN NARKOTIKA JENIS GANJA (TINJAUAN KASUS NO. 63/PID.SUS-ANAK/2015/PN.MDN) - Teresia Simatupang (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2019)
AbstractNarcotics abuse is increasingly widespread. The users are not only from among officials but also underage children so that this can damage their mentality and mindset. For this reason, it is necessary to know the internal and external factors why children consume narcotics, marijuana type, so it can be resolved. Besides, it needs legal arrangements for the underage users of narcotics to be positioned appropriately, that is rehabilitation, according to the provisions of Article 54 of Law Number 35 of 2009 concerning narcotics and law number 11 concerning the juvenile justice system.